ANTIMICROBIAL, ANTIOXIDANT AND ANTIBIOFILM ACTIVITY OF EXTRACTS OF MELILOTUS OFFICINALIS (L.) Pall - K. G. Mladenović; M. Ž. Muruzović; O. D. Stefanović; S. M. Vasić; Ljiljana; R. Čomić (Journal of Animal and Plant Sciences, 2016)
In this paper, the antioxidant and antimicrobial activity, the concentrations of total phenols, flavonoids, tannins and proanthocyanidins in the water, acetone, diethyl ether and ethanol extracts of Melilotus officinalis L. were analysed and their effect on the bacterial biofilm formation. The highest concentration of total phenols (36.25 mgGA/g) and tannins (21.25 mgGA/g) were detected in the water extract. The highest concentration of flavonoids (53.09 mgRU/g) was detected in the acetone extract. Proanthocyanidins were not detected in the water extract, while the highest concentration of these compounds was measured in the acetone extract (3.77 mgCChE/g). The antioxidant and reducing power of the M. officinalis extracts were measured by spectrophotometric method, and all results were compared to vitamin C and water extract of Aronia melanocarpa. The water extract showed the highest antioxidant activity, while the diethyl ether extract the lowest one. The extent of reducing power in the examined extracts was various. The water extract demonstrated the highest activity and the absorbance was from 0.03 to 0.68, while the lowest reducing power was demonstrated in the diethyl ether extract whose absorbance was from 0.04 to 0.20. In vitro antimicrobial activity was tested by microdilution method determining the minimum inhibitory concentration (MIC) and minimum microbicidal concentration (MMC). 25 microorganisms were examined, including 19 species of bacteria and 6 species of fungi. The extracts showed greater effect on G+ bacteria than on the G- bacteria. The acetone extract showed the highest antimicrobial activity. The acetone extract inhibit the biofilm formation of bacteria Proteus mirabilis and Pseudomonas aeruginosa.
Keywords: Melilotus officinalis; antimicrobial activity; antioxidant; phenols; flavonoids; tannins; biofilm